MANAJEMEN LEMBAGA PENJAMIN MUTU STIT MUHAMMADIYAH NGAWI DALAM MENANAMKAN NILAI-NILAI MODERASI BERAGAMA SEBAGAI UPAYA MENJAGA KUALITAS PENGAJARAN DI KAMPUS - Yusron, Hanafi; Gesang Saputra, Alan Lutfi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2024)
Campus Quality Assurance Institutions are responsible for the quality of teaching within their area or scope of responsibility. Quality assurance institutions must be able to manage campus quality. Efforts to instill the values ​​of religious moderation at STIT Muhammadiyah Ngawi really need to be instilled, this is because demographically or demographically, in social life, students interact with people of other religions. Apart from that, students studying at STIT Muhammadiyah Ngawi consist of various community organizations. The aim of this research is to provide an overview of leadership efforts aimed at instilling national values ​​of commitment and tolerance at the STIT Muhammadiyah Ngawi complex. Apart from that, this research aims to explain the influence of the Campus Quality Assurance Institute in fostering the values ​​of national commitment and tolerance in the STIT Muhammadiyah Ngawi campus environment. This investigation used a qualitative naturalistic methodology. The phenomena under consideration originate in pure nature, without any engineering intervention. The research dataset consists of interview transcripts, field notes, photos, and situation settings documented through researcher observations. This research concludes that campus leadership in instilling national commitment and tolerance at the STIT Muhammadyah Ngawi Campus has a positive impact because it is seen in daily life such as carrying out flag ceremony activities, implementing good discipline, carrying out extracurricular activities, carrying out conducive and disciplined learning, not misbehaving. arbitrarily, instilling a sense of empathy, visiting friends if someone is sick, creating a sense of mutual respect among the school community so that a safe, orderly, comfortable school atmosphere is created in carrying out learning activities and instilling the values ​​of tolerance for students which is beneficial for them in social life